Thin RC Shell-Slab Roofing System with Steel Rod Connections - Husain M. Husain; Ashraf. A. Al-Feehan (Engineering and Technology Journal, 2010)
An innovated structural system, namely the Shell-Slab Roofing System(SSRS) of precast thin reinforced concrete cylindrical shell and flat slab has beenfabricated as a roof segmental unit. The flat slab rests on the cylindrical shell at thecrown and also connected to the shell by steel rod connections at each side. Steelplate strips are fixed on the bottom surface of the slab and on the top and thebottom surfaces of the shell as external tensile and shear steel reinforcement toprevent punching shear around the steel rod connections. The ratio of the shellheight to the chord length was (0.1). The structural behavior of the roof system hadbeen investigated under uniformly distributed static load. Experimental work wascarried out by fabrication of six complete segments with scale-down simulationfactor equal to (0.25). The vertical deflections had been observed at selectedpositions on the models. A water/cement ratio of (0.5) combined with a cement:sand ratio of (1:2) had been employed. The influence of certain experimentalparameters had been studied. The model with only twelve rod connections andminimum reinforcement volume ratio was adequate to resist the live loads forbuildings with large span roofing. The investigation showed that the combined unitof thin concrete shell and flat slab with embedded small diameter steelreinforcement was suitable for construction of such roofing system as large spanstructures with lower ratio of shell height to chord length (h/c) equal to (0.1) .